Ultra-Wideband Notched Characteristic Fed by Coplanar Waveguide - Hadinegoro, Rastanto; Ningsih, Yuli Kurnia; Surjati, Indra (Makara Journal of Technology, 2014)
In this paper, a novel Ultra-Wide Band (UWB) notch patch antenna with co-planar waveguide (CPW) fed is presented. This antenna only used one layer and the patch antenna is constructed on the first layer and back to back with CPW fed and bottom part is ground plane. The width notch is used to achieve the UWB characteristic. The results shown that the impedance bandwidth is 1130 MHz (1.662–2.792 GHz) or about 50.7% for VSWR <2.